2020
DOI: 10.1002/ange.201915519
|View full text |Cite
|
Sign up to set email alerts
|

Silicon‐Free SuFEx Reactions of Sulfonimidoyl Fluorides: Scope, Enantioselectivity, and Mechanism

Abstract: SuFEx reactions, in which an S−F moiety reacts with a silyl‐protected phenol, have been developed as powerful click reactions. In the current paper we open up the potential of SuFEx reactions as enantioselective reactions, analyze the role of Si and outline the mechanism of this reaction. As a result, fast, high‐yielding, “Si‐free” and enantiospecific SuFEx reactions of sulfonimidoyl fluorides have been developed, and their mechanism shown, by both experimental and theoretical methods, to yield chiral products. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…Very recently, the mechanism of the Si-free SuFEx reaction with phenolate anions was investigated with the help of density functional theory (DFT), and an addition–elimination mechanism with very low barriers and early transition states was found while an S N 2-type reaction could not be excluded under experimental conditions. 26 The authors also concluded that the very high reactivity of the phenolate anion probably leads to a different mechanism compared to less strong nucleophiles, as investigated here.…”
Section: Introductionmentioning
confidence: 49%
“…Very recently, the mechanism of the Si-free SuFEx reaction with phenolate anions was investigated with the help of density functional theory (DFT), and an addition–elimination mechanism with very low barriers and early transition states was found while an S N 2-type reaction could not be excluded under experimental conditions. 26 The authors also concluded that the very high reactivity of the phenolate anion probably leads to a different mechanism compared to less strong nucleophiles, as investigated here.…”
Section: Introductionmentioning
confidence: 49%
“…Very recently, the mechanism of the Si-Free SuFEx reaction with phenolate anions was investigated with the help of density functional theory (DFT) and an addition-elimination mechanism with very low barriers and early transition states was found while an SN2-type reaction could not be excluded under experimental conditions. [25] The authors also concluded that the very high reactivity of the phenolate anion probably leads to a different mechanism compared to less strong nucleophiles as investigated here.…”
Section: Methodsmentioning
confidence: 61%
“…sulfonimidamides, and sulfonimidates. 61,62 So we treated it with C-nucleophile as an selected example to construct the n-butyl substituted sulfoximine compound 21 without the erosion of the enantioselectivity (Figure 5b), considering sulfoximines were known as a rising star in drug discovery, which also represents the first example from aryl sulfoximine to alkyl sulfoximine. 63,64 Furthermore, we realized the iterative addition of 3b which gave a compound 23 with two carbon stereocenters and two sulfur stereocenters (Figure 5c).…”
Section: Difluoro(aminosulfinyl)methylationmentioning
confidence: 99%